Scientific Writing and Journal publications: Practical Hints and Tips. A Review Article. - El Mustafa, Osman Mohamed; El Mustafa, Mohamed O. M. (مجلة الجزيرة للعلوم الصحية; مجلد 13 عدد 2 (2017), 2017)
This review article is intended to highlight the importance of scientific writing and journal publications for career development of university students, postgraduate students, medical and university staff. Scientific writing facilitates the exchange of knowledge and experience.          The authors reviewed the literature and summarized the important practical hints and tips to aid producing a publishable scientific material. The authors concluded that scientific writing is an art which is mastered by practice, perseverance and the will to continue.